Pengaruh Perilaku Mahasiswa terhadap Ketertarikan Literasi Buku Fisik dalam Lingkungan Pembelajaran Akademik - Sarifah, Lailatus; Khoirunnisa, Novita Aulia; Rahayu, Nina Muji; Mareta, Nayla Rizky; Nurhalimah, Siti; Nugraha, Joko Tri (ANTASENA: Governance and Innovation Journal, 2026)
This study aims to analyze the influence of student behavior on interest in physical book literacy within the academic learning environment in the digital era. The development of information technology has changed students’ literacy patterns, causing digital media to become more dominant in academic activities. However, physical books still play an important role in helping students understand learning materials more deeply. This research employed a quantitative approach with an explanatory research design. The sampling technique used probability sampling through a simple random sampling method involving 75 active students of the Public Administration Study Program. Research data were collected through questionnaires using a four-point Likert scale and analyzed using descriptive statistics, validity tests, reliability tests, simple linear regression analysis, and hypothesis testing using IBM SPSS Statistics 27. The results showed that 72% of students predominantly used digital media because it is considered practical and easily accessible. However, physical books are still used to understand theoretical materials and improve learning concentration. In addition, 69% of respondents used a combination of digital media and physical books in the learning process. The regression test results indicated that student behavior significantly influences interest in physical book literacy within the academic environment. The findings show that digital media and physical books complement each other in supporting the quality of student learning and maintaining academic literacy culture in higher education institutions during the digitalization era.